OCCURRENCE STUDY OF BLACKTIP REEF SHARK (Carcharhinus melanopterus) IN THE WATERS OF GILI PETELU, EAST LOMBOK DISTRICT: STUDI KEMUNCULAN HIU KARANG SIRIP HITAM (Carcharhinus melanopterus) DI PERAIRAN GILI PETELU, KABUPATEN LOMBOK TIMUR - Jayawangsa, Rahman; Larasati, Chandrika Eka; Himawan, Mahardika Rizqi; Rafandi, Muhammad Tezar (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Gili Petelu is one of the aggregation sites for marine species such as blacktip reef sharks. This study aims to determine the habitat characteristics of blacktip reef sharks in the waters of Gili Petelu, East Lombok Regency. This research was conducted from November to December 2023. Observations of blacktip reef sharks were carried out using two methods, namely UVC (underwater visual census) and accidental sampling. The UVC (underwater visual census) method was carried out by swimming on the east side of the island for approximately 170 m with a width of 10 m to the left and right. The use of the accidental sampling method is done to find out or observe the appearance of blacktip reef sharks that are outside the transect. Data collection of coral reef cover was carried out using the UPT (underwater photo transect) method, which was then analyzed using CPCe software. In addition, water conditions observed during the study were salinity, temperature, pH, and current speed. Based on the observation results, there were 87 encounters with the Carcharhinus melanopterus shark species in the water area. In the blacktip reef shark encounter area, it is known that there are locations dominated by soft coral, sand, coral breaks, and areas with hard coral. Based on water conditions, most shark individuals were found in water conditions with a pH of 8, current speed 0.27-0.35 m/s, salinity 30, and a temperature range of 28-29°C, with a total of 24 individuals found.